Design and validation of an immersive virtual rehabilitation system for individuals with vestibular disorders: A feasibility study - Abdulaziz Ibrahem-Altwijri; Sergio Albiol-Pérez; María-Dolores Cortés-Vega; Cristina García-Muñoz; Rocio Sasián Ramírez de Arellano; José-Antonio Gil- Gómez; José-Antonio Lozano-Quilis; María Jesús Casuso-Holgado (PLoS ONE, 2026)
Background Vestibular rehabilitation is an essential part of managing balance disorders, but traditional exercises can often be repetitive and demotivating for patients. This can reduce adherence and limit treatment outcomes. Objective This study aimed to assess the feasibility, usability, patient satisfaction, and safety of DizzyVR, an immersive virtual reality system designed to support vestibular rehabilitation. Preliminary data on its potential effects on clinical outcomes were also collected. Methods A prospective, single-arm feasibility study was conducted with ten participants diagnosed with various vestibular disorders. Each participant completed eight weekly sessions using DizzyVR. Feasibility was assessed through session attendance and completion rates. Usability, satisfaction, and safety were measured using the System Usability Scale, the User Satisfaction Evaluation Questionnaire, and the Simulator Sickness Questionnaire. Clinical measures included the Dizziness Handicap Inventory (DHI), Timed Up and Go (TUG) test, Activities-specific Balance Confidence (ABC) scale, and Functional Gait Assessment (FGA). Results Ten participants completed the training, with a high adherence rate (91.25%). Usability scores indicated good ease of use, and satisfaction scores were high. Mild adverse events such as nausea or disorientation were reported by three participants, but improved over time. Exploratory pre–post changes were observed in gait speed (TUG: p = 0.002), balance confidence (ABC: p = 0.007), and gait stability (FGA: p = 0.012). While DHI scores demonstrated a trend toward improvement, the change did not reach statistical significance (p = 0.081). Overall, participants reported feeling safe and expressed willingness to recommend and reuse the system. Conclusions The findings suggest that DizzyVR is a feasible, usable, and well-accepted tool that may complement conventional vestibular rehabilitation. The system appears to support patient motivation and safe participation while showing promising exploratory changes in balance and gait. Further studies with larger samples, control groups, and longer follow-up are recommended to confirm and expand on these promising preliminary results.